Hip Hop, empowerment, and clinical practice for homeless adults with severe mental illness. Issue 2 (3rd April 2019) - Travis, Raphael; Rodwin, Aaron H.; Allcorn, Ashley
ABSTRACT: This article focuses on the use of a music and empowerment-based group as a vehicle for engagement, and therapeutic, and social-emotional benefits with homeless adults coping with severe mental illness in a shelter setting. The authors present a conceptual framework that includes case illustrations to capture the group process. The group was guided by the MUZUZE Hip Hop and empowerment framework, which is meant to facilitate well-being as evidenced by indicators of social-emotional learning and empowerment-based positive youth development. The authors found that the use of Hip Hop helped foster well-being via pathways of individual and community empowerment. Implications for future research and practice are discussed.